Close Relationship between the 2009 H1N1 Virus and South Dakota AIV Strains - Li, Cun; An, Xiao-ping; Mi, Zhi-qiang; Liu, Da-bin; Jiang, Huan-huan; Pan, Bo; Wang, Sheng; Chen, Bin; Tong, Yi-gang (Virologica Sinica, 2011)
Although previous publications suggest the 2009 pandemic influenza A (H1N1) virus was reassorted from swine viruses of North America and Eurasia, the immediate ancestry still remains elusive due to the big evolutionary distance between the 2009 H1N1 virus and the previously isolated strains. Since the unveiling of the 2009 H1N1 influenza, great deal of interest has been drawn to influenza, consequently a large number of influenza virus sequences have been deposited into the public sequence databases. Blast analysis demonstrated that the recently submitted 2007 South Dakota avian influenza virus strains and other North American avian strains contained genetic segments very closely related to the 2009 H1N1 virus, which suggests these avian influenza viruses are very close relatives of the 2009 H1N1 virus. Phylogenetic analyses also indicate that the 2009 H1N1 viruses are associated with both avian and swine influenza viruses circulating in North America. Since the migrating wild birds are preferable to pigs as the carrier to spread the influenza viruses across vast distances, it is very likely that birds played an important role in the inter-continental evolution of the 2009 H1N1 virus. It is essential to understand the evolutionary route of the emerging influenza virus in order to find a way to prevent further emerging cases. This study suggests the close relationship between 2009 pandemic virus and the North America avian viruses and underscores enhanced surveillance of influenza in birds for understanding the evolution of the 2009 pandemic influenza.